Precise ro-vibrational analysis of vibrational bands in 1100-1400 CM-1 region of spectrum of C2HD3; Перспективы развития фундаментальных наук; Т. 1 : Физика - Kashirina N. V. Nadezhda Vladimirovna (2017, 2017)
Заглавие с экрана